Campaign Spending and Electoral Integrity: Assessing the Plausibility of the Challenger Spending Efficacy Advantage in Irish & British Elections - DUGGAN, ALAN MARTIN (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2020)
Do incumbents lose ground to challengers even when their spending is evenly matched? Much of the literature points to a spending efficacy advantage for challengers (i.e. non-incumbents glean more from spending than incumbents). The causal mechanism for this advantage has been identified by many studies as a greater return on spending that increases name recognition. This finding originates in research on the USA (Jacobson 1978, 1985, 1990) but has been found in many other contexts such as Ireland (Benoit and Marsh 2010) and the UK (Johnston and Pattie 2006). This thesis assesses the plausibility of the challenger spending advantage in elections to the UK House of Commons, Irish D?il, Scottish Parliament, and Welsh Assembly using a novel dataset comprising approximately 18,500 observations. The analysis casts doubt on the credibility of the challenger spending advantage in the cases studied by offering context specific theoretical arguments and using innovative matching techniques to manage problematic spending data. Additionally, this thesis offers analysis of differential spending effects for male and female candidates in Irish and British elections. Previous literature on differential spending effects based on gender is heavily US centric and returns mixed results. This thesis seeks to expand this arena of analysis to the four contexts under investigation and finds little evidence of differential spending efficacy for male and female candidates. Findings on spending efficacy related to both incumbency and gender have significant implications for campaign spending regulation and electoral integrity.
APPROVED
Keywords: Campaign Spending; Campaign Finance; Electoral Politics